The Influence of Specialty Coffee Bean Packaging Design on Consumer Purchase Intention - Arayhan, Balthazar; Hudrasyah, Herry (Journal of Business and Management, 2021)
Back when Starbucks first emerged, people finally had access to better tasting coffee and recently, people got the chance to taste even better tasting coffee due to the commercialization of specialty coffee. This is due to the third wave of coffee where people interests in higher quality coffee hugely increased compared to the first and second wave. The third wave is characterized by increased awareness in the coffee qualities, as the producers and consumers are more educated regarding coffee. Various coffee roasters from around the world started to emerge selling whole specialty coffee bean in a packaging. The design of the packaging varies from roasters to roasters but all of them designed them with the purpose of attractingthe consumers. With researches regarding packaging is numerous, there is yet one regarding specialty coffee bean packaging. Therefore, this study researches the subject specialty coffee bean to see if the packaging influences purchase intention or not. This study used quantitative methods as its means to find the answers. Of 250 respondents gathered, then processed with SPSS software to conduct regression analysis and importance – performance analysis. The output was that there is indeed an influence of packaging elements (graphic, color, typography, and image) on the consumer purchase intention. Further analysis with importance-performance analysis shows that graphic is of highest importance according to the respondents along with composition as the most attractive attribute to the respondents. These finding are expected to be considered by coffee roasters in improving their packaging design based on these statistical findings.Keywords: Specialty coffee bean, packaging design, purchase intention, importance-performance analysis